Features of the expression of cyclin D1 and oncoprotein p27 in oropharyngeal squamous cell carcinomas with different proliferative potential - Rakhmanov , V.V.; Shponka , I.S. (Морфологія / Morphologia / Morfologìâ, 2025)
Background. Squamous cell carcinoma of the head and neck, including oral, pharyngeal, larynx, and sinonasal tract cancers, is the sixth most common cancer worldwide. The development of malignant tumors is associated with a series of changes in the activity of cell cycle regulators, which can be considered as positive and negative regulators. Positive regulators of the cell cycle can be considered cyclin A and cyclin D1, which contribute to the transition of the cell cycle from one phase to another; others, such as oncogene suppressors Rb, p16, p53, p21 and p27 are negative regulators that stop the cell cycle in the S phase. The aim of the study was to compare the expression levels of markers p27 and cyclin D1 in HPV-positive (p16+) and HPV-negative (p16-) squamous cell carcinomas of the oropharynx with different proliferative potential. Methods. In the work, the biopsy and surgical material of squamous cell carcinomas of 70 patients (22 women and 48 men) who were treated in the KP "Dnipropetrovsk Regional Clinical Hospital named after I.I. Mechnikova Hospital of Dnipro in the period from 2019 to 2022. The age of the patients ranged from 41 to 80 years; the average age was 59.75±9.16 years. Primary monoclonal antibodies to p16 (RTU), p53 (RTU), Cyclin D1 (EP12, RTU), Ki-67 (sp6, RTU), p27 (sp1, RTU) and the UltraVision Quanto imaging system (LabVision) were used for immunohistochemical study. Results and conclusion. Cyclin D1 marker, analyzed in groups ≤10% and >10% according to clinical and morphological indicators showed a statistically significant difference in age (p<0.05) and histological type (keratinized/non-keratinized), (p<0.05) ; the analysis of cyclin D1 expression showed an inverse trend to the p16/HPV status, the largest number of 80.85% of cases of squamous cell carcinomas of the oropharyngeal area cyclin D1 with >10% were found among p16/HPV (-) observations; 91.30% of cases of squamous cell carcinoma of the oropharyngeal area with cyclin D1 ≤10% had p53 expression below the level of 25% (p<0.05); the largest number of cases of p27 expression with a high score (2+,3+) was noted among patients aged 40-49 years (p<0.05).